Identifikasi Bahaya Dan Pengendalian Resiko di Area Produksi Penambangan: Hazard Identification And Risk Control in Mining Production Areas - Yusril, Yusril (Journal of Engineering Science and Technology Applications, 2024)
Mining companies have provided a level of security related to OHS, but there are still work accidents, occupational diseases, fires, explosions, avalanches, and the environment. Thei causei of worki accidentsi is determined byi thei actionsi ofi peoplei whoi doi noticomplyi withi worki safetyi (unsafei actions) and environmental conditions (unsafe conditions). Thei purposei of thisi studyi is to idetermine the potentiali hazardsi in mining activities and control controls in mining activities. This researchi iwas conductedi at PT Bumi Sentosa Jaya, locatedi ini Boedingi iVillage, Lasoloi Islandsi iDistrict, iNorth Konawei iRegency, Southeasti Sulawesii iProvince. The research was conducted usingi the HIRARCi (Hazardi iIdentification, Riski Assessmenti, and Riski iControl) imethod. Data on hazardi and riski controli are processed using the semi-quantitative.The findings were 20 potential hazards, with an incident rating obtained Extremely low 0%, Priority 20%, Medium 65%, Acceptable 15%After controlling the risk, the residual risk obtained is 40%. 60% is acceptable. Control is carried out by hierarchical control, consisting of engineering, administrative, work practices, and control methods.